(untitled) (Світ фінансів, 2017)
Гапонюк М. А. Окремі аспекти боргової політики органів місцевого самоврядування. Розкрито передумови та деструктивні чинники розвитку ринку місцевих запозичень в Україні. Проаналізовано вплив світової економічної кризи на ринок муніципальних запозичень України. Окреслено стратегічні вектори боргової політики органів місцевого самоврядування в Україні. Haponyuk M. Some aspects of promissory policy of local self-goverment organs in Ukraine. Pre-conditions and destructure factors of market of the local borrowings development in Ukraine are exposed. Influence of world economic crisis on the market of the municipal borrowings of Ukraine is analysed. Strategic vectors of promissory policy of local self-government organs are outlined.